STEM/STEAM interests of Spanish secondary students in rural and urban areas (Educação e Pesquisa, 2022)
This study analyses the main areas of knowledge that Spanish secondary education (ESO) students want to develop in the future. The article focuses on STEAM subjects and the specific context of students, such as the population of their town or city, career expectations and gender. The research follows a quantitative design based on data collected through a questionnaire created for this analysis. The sample was based on a casual non-probabilistic group of 608 students in 2nd, 3rd and 4th ESO from Asturias (Spain). The study highlights student interests in careers related to Science, Technology, Engineering, Arts and Mathematics, as well as significant mismatches between student aspirations and educational goals in the STEAM model. In this sense, these interests are so varied that it suggests a deficit when it comes to identifying the interdisciplinary synergy and commonalities among these topics. The findings show the different academic and career aspirations according to gender, academic level, and rural or urban areas of residence, highlighting a high level of indecision when choosing a specific branch of knowledge, in line with their future careers.